Clinical and epidemiological study of onychomycosis among patients of the national institute of hygiene in rabat, Morocco (2016-2020) - Majda El Abbassi; Hajar Boughroud; Fatima Amarir; Mohamed Rhajaoui; El Bachir Adlaoui; Hanane Mkinsi; Imane Baha; Samira Rais (Mazandaran University of Medical Sciences, 2024)
Background and Purpose: Onychomycosis is a common nail infection characterized by the discoloration, thickening, and detachment of nails. This study aimed to provide valuable insights into this pathology by assessing its prevalence, clinical aspects, related comorbidities, and causative agents in patients from a Moroccan population.Materials and Methods: This retrospective study was conducted on 1,606 subjects at the Mycology-Parasitology laboratory of the National Institute of Hygiene in Rabat, Morocco, over five years (2016-2020). Nail samples were collected from both fingernails and toenails and processed through microscopic examination and culture. The incubated tubes were kept at a temperature range of 28-30°C for 4-5 weeks.Results: Onychomycosis was mycologically confirmed in 1,794 samples (93.24%). It occurred commonly in the 41-60 age group, with a higher incidence among females (74.53%). Diabetes, alongside other chronic diseases, was prevalent among patients with underlying conditions, comprising 131 cases (40.56%). Disto-lateral subungual onychomycosis emerged as the most prevalent clinical presentation, comprising 1,536 cases (79.92%). Fingernails primarily affected by yeasts, notably Candida albicans, accounted for 565 cases (29.80%), while toenails were predominantly impacted by dermatophytes, primarily Trichophyton rubrum (n=1,230, 64.87%). Mixed infections exclusively featured yeasts and dermatophytes, predominantly T. rubrum and C. albicans, which accounted for 79 (4.40%) cases. The study explored the influence of molds, yielding insights into their rarity in onychomycosis.Conclusion: These findings hold significant implications for the clinical management and diagnosis of onychomycosis, particularly in patients with underlying chronic conditions. Further epidemiological studies across Morocco are needed for meaningful comparisons.